2021
DOI: 10.1128/mbio.01518-21
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Proteases Control the Timing of Aggregative Community Formation in Vibrio cholerae

Abstract: Bacteria can work as collectives to form multicellular communities. Vibrio cholerae , the bacterium that causes the disease cholera in humans, forms aggregated communities in liquid. Aggregate formation relies on a chemical communication process called quorum sensing.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 45 publications
(68 reference statements)
1
11
0
Order By: Relevance
“…The vca081 2 and vca0813 genes are located adjacent to one another in an operon on the V. cholerae chromosome and encode the multidomain proteins LapX (Uniprot KB Q9KLD4) and Lap (Lap, Uniprot, KB: Q9KLD3; EC 3.4.11.10), respectively ( 15 ) ( Fig. 1 , A and B ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The vca081 2 and vca0813 genes are located adjacent to one another in an operon on the V. cholerae chromosome and encode the multidomain proteins LapX (Uniprot KB Q9KLD4) and Lap (Lap, Uniprot, KB: Q9KLD3; EC 3.4.11.10), respectively ( 15 ) ( Fig. 1 , A and B ).…”
Section: Resultsmentioning
confidence: 99%
“…1 A ). Previous work showed that while LapX and Lap are required for V. cholerae aggregation, GbpA is not ( 15 ); hence we focus here on LapX and Lap. LapX is a leucine aminopeptidase-related protein, a putative serine protease that belongs to the subfamily A of the S1 family of the PA clan proteases.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations